Ultrawideband radar : applications and design (Boca Raton, Florida : CRC Press, 2012)
This book outlines the latest advances in the theory, design, and implementation of ultrawideband (UWB) radar technology, which shows promise for use in diverse applications ranging from toilet flushing sensors and cancer detection equipment to radar sensors that could be used in homes, public places, cars, hospitals, and aircraft. Detailing their potential for use in medicine, security, and other key areas, the book covers topics including the technology's history and government regulation internationally. It also discusses propagation theory and examples of precision ranging as applied to material penetration, imaging, and additional medical applications
Chapter 1 -- Introduction to Ultrawideband Radar Applications and Design Chapter 2 -- Development of Ultrawideband Communications Systems and Radar Systems Chapter 3 -- Signal Waveform Variations in Ultrawideband Wireless Systems: Causes and Aftereffects Chapter 4 -- American and European Regulations on Ultrawideband Systems Chapter 5 -- Principles of Materials-Penetrating Ultrawideband Radar Systems Chapter 6 -- Ultrawideband and Random Signal Radar Chapter 7 -- Automatic Measurement of Ground Permittivity and Automatic Detection of Object Location with GPR Images Containing a Response from a Local Object Chapter 8 -- UWB Pulse Backscattering from Objects Located near Uniform Half-Space Chapter 9 -- Medical Applications of Ultrawideband Radar Chapter 10 -- Large Current Radiators: Problems, Analysis, and Design Chapter 11 -- Novelda Nanoscale Impulse Radar Chapter 13 -- Holographic Subsurface Radar Technology and Applications Chapter 14 -- Xaver Through -Wall UWB Radar Design Study Chapter 15 -- The Camero, Inc., Radar Signal Acquisition System for Signal-to-Noise Improvement Chapter 16 -- The Camero, Inc., Time Delay Calibration System for Range Cell Synchronization Chapter 17 -- The Camero, Inc., UWB Radar for Concealed Weapons Detection
Includes index.
Keywords: ULTRA-WIDEBAND RADAR